Pelatihan Teknik Fotografi Untuk Meningkatkan Kualitas Foto Produk UMKM Kelurahan Nginden Jangkungan - Muhammad Luthfi Fakhri; Acep Samsudin (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Online stores can reach larger target customers more quickly and accurately, and do so more efficiently and effectively, making it one of the most popular sales channels today. In today's digital marketing era, goods sold online sell better than goods sold on marketplaces. One of the disadvantages of online shopping is that you cannot immediately see what you want to buy, so product visualization or appearance is very important to attract customer buying interest. Good product photos will increase product sales. Shooting techniques, lighting, props/decorations that make it look attractive will affect the quality of product photos when marketed to potential buyers. Through this product photography training, MSMEs in Nginden Jangkungan village will improve their skills and increase their knowledge of good product photography techniques.